PENGARUH LEVERAGE, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP PAJAK PENGHASILAN BADAN DENGAN BIAYA OPERASIONAL SEBAGAI VARIABEL MODERASI STUDI KASUS SEKTOR PERUSAHAAN KEUANGAN - Sekartaji, Citra Dewi Putri; Arifin, Atwal (LPPM Universitas Bina Bangsa, 2024)
In the tax system, corporate income tax is a significant type of tax. Law number 36 of 2008 concerning income tax states that corporate income tax is imposed on tax subjects for income received or earned in the tax year. It is necessary to understand how certain factors can influence the amount of income tax that must be paid by financial sector companies registered on the IDX in the 2019-2022 period. The factors that are the focus of the research are leverage (debt ratio), company profitability, and capital structure. Apart from that, the research will also examine whether operational costs act as a moderating variable that can influence the relationship between leverage, profitability, and capital structure and corporate income tax. This research aims to analyze and test the influence of Leverage, Profitability and Capital Structure which have a positive and significant influence on corporate income tax